Non-linear shear behaviour of bovine cortical bone by coupling the Arcan test with digital image correlation. (November 2018) - Xavier, J.; Morais, J.; Pereira, F.
Highlights: Non-linear shear behaviour of bone tissues is experimentally addressed. Predominant shear behaviour at the gauge section is shown by DIC. The classical data reduction is enhanced from full-field measurements. Evaluation of shear modulus without need of correction factors. Shear modulus, shear strength and Ramberg–Osgood parameters of cortical bone are determined. Abstract: The non-linear shear behaviour of bovine cortical bone is measured by coupling the Arcan test with digital image correlation. The experimental study is carried out on specimens taken from bovine femur and oriented along the longitudinal-tangential material plane. An a d hoc Arcan fixture is built to transfer the cross-head displacement of the testing machine into a shear loading at the centre of the V-notched section. A validation of predominant shear behaviour at the gauge section is shown from full-field deformation measurements. Moreover, direct evaluation of the shear modulus is obtained by integrating the shear strain component along the V-notches, avoiding numerical correction factors required in the classical data reduction scheme. The shear modulus of bovine cortical bone is found in good agreement with references from literature. Moreover, the shear stress at maximum load is understood as a suitable estimation of the shear strength. Furthermore, the Ramberg–Osgood model is found to provide an accurate description of the non-linear shear behaviour of bone tissue.